Association between vascular injury identified via echo-Doppler examination and talus fracture-dislocation - Ferreira, Andresa Ramires Hoshino; Barroco, Rui dos Santos; de Freitas, Álvaro Diego Pupa; de Miranda, Bruno Rodrigues; Oliveira, Letícia Zaccaria Prates de; Abdul Ghani, Mahmoud Beerens (Scientific Journal of the Foot & Ankle, 2018)
Objective: To investigate the association between talus fracture-dislocation and the occurrence of pre-operative vascular injuries identified via echo-colour Doppler examination of the lower limbs and to assess whether these injuries directly affect talar necrosis. Methods: Retrospective study with data collection on 26 patients with a diagnosis of talus fracture-dislocation who were evaluated by pre-operative arterial and venous echo-colour Doppler from 2004 to 2015. Results: The sample included 26 patients (26 feet), ranging in age from 16 to 62 years, with a mean follow-up time of 2 years and 9 months. A total of six (23.07%) changes were diagnosed via echo-colour Doppler, of which five (83.33%) were due to arterial injury of the ‘segmental occlusion of the posterior tibial artery’ type and one (16.67%) was due to venous injury of the ‘recent deep venous thrombosis of the popliteal-distal segment’ type, with no arterial injury. No significant association was found between the vascular injuries diagnosed by Doppler and progression to necrosis. Conclusion: A significant portion of the patients with talus fracture-dislocation presented with vascular injury diagnosed by echo-colour Doppler, although no association was found between vascular injury and outcomes of osteonecrosis. Level of Evidence IV; Diagnostic studies.